2012
DOI: 10.1186/preaccept-4284799146146604
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic wasp responses to symbiont-based defense in aphids

Abstract: Here we show that the parasitic wasp A. ervi discriminates among symbiont-infected and uninfected aphids, and changes its oviposition behavior in a way that increases the likelihood of overcoming symbiont-based defense. More generally, our results indicate that natural enemies are not passive victims of defensive symbionts, and that an evolutionary arms race between A. pisum and the parasitoid A. ervi may be mediated by a bacterial symbiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 1 publication
(1 reference statement)
0
43
1
Order By: Relevance
“…The differences between the two wasps may reflect different interactions between the fly, wasp and endosymbiont, including the possible effect of Lb superparasitism (e.g., injection of larger venom amounts through repeated oviposition may counter the effects of Spiroplasma). For example, the parasitoid wasp Aphidius ervi intentionally superparasitizes endosymbiontinfected aphids, presumably to overcome the symbiont-encoded defense (Oliver et al, 2012). In our study, however, the higher superparasitism of Lb compared with Lh does not seem to result in higher wasp survival.…”
Section: Wasp-killing Mechanismcontrasting
confidence: 53%
“…The differences between the two wasps may reflect different interactions between the fly, wasp and endosymbiont, including the possible effect of Lb superparasitism (e.g., injection of larger venom amounts through repeated oviposition may counter the effects of Spiroplasma). For example, the parasitoid wasp Aphidius ervi intentionally superparasitizes endosymbiontinfected aphids, presumably to overcome the symbiont-encoded defense (Oliver et al, 2012). In our study, however, the higher superparasitism of Lb compared with Lh does not seem to result in higher wasp survival.…”
Section: Wasp-killing Mechanismcontrasting
confidence: 53%
“…Microbial effects on animal chemistry also recently have been linked to changes in predator-prey interactions ( 11) and feeding behavior ( 12). Females of the African malaria mosquito, Anopheles gambiae, use chemical cues released from human skin to locate hosts.…”
Section: Perspectivesmentioning
confidence: 99%
“…Defensive endosymbionts that protect their host from parasitism can modify competitive relationships among parasitoid species . However, parasitoids can detect whether or not a potential aphid host carries a protective symbiont (Oliver et al, 2012); this could result in the parasitoid switching to its alternative host, leading to apparent competition. Frago et al (2017) recently found that plants attacked by pea aphids carrying the endosymbiont Hamiltonella defensa released lower quantities of volatiles, hence recruiting fewer parasitic wasps and thus increasing aphid fitness.…”
Section: Endosymbionts Mediate Host-parasitoid Non-trophic Interactionsmentioning
confidence: 99%